Secondo Convegno Nazionale della Società Italiana di Scienze Sensoriali Atti dei LavoriMilano, 30 giugno - 1 luglio 2008 - Mario Bertuccioli (Proceedings e report, 2008)
Over the last decade there has been a growing interest in sensory science in Italy. This has clearly resulted in an increase in the number of researchers engaged in this sector and the number of companies that exploit sensory evaluations for product innovation and enhancement and in quality control. In Italy, in the sphere of the valorisation of prestige foodstuffs there is an increasing sensitivity towards the adoption of strict methods for describing the sensory properties of the products and ascertaining compliance with defined sensory standards. The Società Italiana di Scienze Sensoriali has played a decisive role in activating and guiding this development. Pursuing this approach, in 2008 the Society organised the 2nd National Convention as an occasion for exchange among professionals working in the field of sensory science.